TIFF images of rock glacier surface velocities for Valley Calchaquíes region, Salta Province, Argentina - Jan Henrik Blöthe; Daniel Falaschi; Sebastián Vivero; Takeo Tadono (PANGAEA, 2024)
For the Valles Calchaquíes region, Northwestern Argentina, we derived rock glacier surface velocities (in unit m/a) from multi-temporal aerial and satellite imagery using a feature tracking approch. The data covers three epochs (EPs), EP1 from 1968 to 2009, EP2 from 2009/2010 to 2020, EP3 from 2020 to 2023. Given the variable availablility of aerial and satellite images, the spatial coverage is not the same for all three EPs and the limit of detection is spatially variable. For our analysis, we used rock glacier outlines as published by the Inventario Nacional de Glaciares of Argentina (https://www.glaciaresargentinos.gob.ar/; polygon data can be downloaded there) that have a minimum area of 0.02 km^2. We provide seperate data sets, one per epoch containing all derived average rock glacier velocities (unit m/a), and one only containing rock glacier velocities that exceed the limit of detection (unit m/a) of our analysis (see publication for details). While the data containing all derived average velocities is intended to document where feature tracking was performed, the data containing rock glacier velocities exceeding the limit of detection shall be used for analysis.